Assessing Patient-Centered Care in Indonesia: Patients’ Perceptions and Key Factors in Private vs Public Hospitals - Johanes Polla; Harjanto Prabowo; Sutoto; Sri Bramantoro Abdinagoro (Jurnal Kesehatan Masyarakat, 2026)
Patient‑Centered Care (PCC) improves health literacy, adherence, and satisfaction, yet its implementation across Indonesian hospital types remains unclear. The reseaech aim to compare patients’ perceptions of PCC and identify associated determinants in public versus private hospitals in Jakarta and its suburbs. A multi‑centre cross‑sectional survey was administered in September 2024 to 500 in‑patients (250 public, 250 private) selected via multistage random sampling from three public and two private hospitals. The validated Picker‑Harvard 34‑item tool measured eight PCC dimensions; provider‑ and institution‑related factors were captured through 15 supplementary items. Data were analysed using descriptive statistics and multivariable logistic regression (α = 0.05). Private hospitals outperformed public hospitals on all structural and process indicators, yielding higher aggregate Patient‑Centered Healthcare Performance (PCHCP) scores (90.8 % vs 78.4 %). The largest gaps concerned access to services (OR 3.4; 95 % CI 2.3–5.0) and respect for patient preferences (OR 3.1; 95 % CI 2.1–4.6). In public hospitals, poor PCC was independently predicted by low education (AOR 2.8), suburban residence (AOR 2.1), limited involvement in decision‑making (AOR 2.7), and difficult access (AOR 5.1). In private hospitals, inadequate care‑plan information (AOR 4.1) and restricted privacy (AOR 3.2) were key drivers of dissatisfaction. While private facilities demonstrate superior PCC, critical deficiencies in communication and shared decision‑making persist in both sectors. Targeted interventions—information transparency, structured medication counselling, streamlined access, and privacy enhancement—are essential for elevating PCHCP scores, particularly in public hospitals, and should be embedded within national hospital quality regulations.